2016
DOI: 10.1080/09585192.2016.1192052
|View full text |Cite
|
Sign up to set email alerts
|

How much does job autonomy vary across countries and other extra-organizational contexts?

Abstract: 1 This paper integrates the study of contextual influences on job autonomy as a key workplace practice with the growing literature on intra-country variation (ICV) versus between-country variation (BCV) in international HRM. While contexts such as industry or country are widely recognized to affect workplace practices such as job autonomy, the influences of different extra-organizational contexts are seldom examined simultaneously or their relative influence systematically compared. Similarly, while much resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 107 publications
0
8
0
Order By: Relevance
“…While the popularity of autonomy as a powerful motivating force in organizations continues to grow, empirical evidence of its impact has offered some conflicting results, leading some to question the wisdom of autonomy in the absence of order (De Waal, 2008). In particular, the HRM literature has highlighted that the benefits in terms of efficiency and performance must be considered alongside the potential pitfalls of decreases in monitoring and control (Van Hoorn, 2018). This study set out to investigate how both autonomy and accountability can play a role in the relationship between empowering leadership, motivation and work performance.…”
Section: Discussionmentioning
confidence: 99%
“…While the popularity of autonomy as a powerful motivating force in organizations continues to grow, empirical evidence of its impact has offered some conflicting results, leading some to question the wisdom of autonomy in the absence of order (De Waal, 2008). In particular, the HRM literature has highlighted that the benefits in terms of efficiency and performance must be considered alongside the potential pitfalls of decreases in monitoring and control (Van Hoorn, 2018). This study set out to investigate how both autonomy and accountability can play a role in the relationship between empowering leadership, motivation and work performance.…”
Section: Discussionmentioning
confidence: 99%
“…This is a major limitation because organizations, large ones in particular, are often considered multicultural and varied in their institutional contexts (e.g. Gregory, 1983;Phillips & Tracey, 2009), with local internal contextual factors having recently been proposed as equally important to national dissimilarities in explaining how contextual influences affect organizations that adopt HRM practices (see Brewster, Mayrhofer, & Smale, 2016;Delbridge, Hauptmeier, & Sengupta, 2011;Thunnissen & Buttiens, 2017;Tung & Baumann, 2009;van Hoorn, 2018). More empirical research that considers the internal context, and in doing so incorporating an awareness of local contextual factors, is thus needed.…”
Section: Introductionmentioning
confidence: 99%
“…Morris and Snell, 2011), contingency perspectives (e.g. Cogin and Williamson, 2014;Mohamed et al, 2013;Smale et al, 2012;Van Hoorn, 2018) and institutional theoretical perspectives (e.g. Belizon et al, 2013;Cox and Warner, 2013;Haak-Saheem et al, 2017;Ma et al, 2016;Prince et al, 2011) were also frequently observed.…”
Section: Research Perspectives Topics and Theoriesmentioning
confidence: 99%